2022
DOI: 10.3389/fmed.2022.899544
|View full text |Cite
|
Sign up to set email alerts
|

Non-cancer Causes of Death Following Initial Synchronous Bone Metastasis in Cancer Patients

Abstract: PurposeTo investigate the non-cancer causes of death (COD) in cancer patients with synchronous bone metastasis (BM) that is based on the Surveillance, Epidemiology, and End Results (SEER) database.MethodsThe retrospective cohort study included malignant cancer patients with synchronous BM diagnosed from 2010 to 2018 in the SEER database. The frequencies and proportion of non-cancer COD were calculated and analyzed in different genders, ages, and races subgroups.ResultsA total of 97,997 patients were deceased a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Our previous analysis showed that non-cancer causes covered 6.9% of patients diagnosed with malignant cancer with synchronous bone metastases. Common non-cancer COD included cardiovascular and cerebrovascular diseases, COPD and associated conditions, and septicemia, infectious and parasitic diseases [5] . The population-based cohort study based on the SEER database focusing on the COD during prostate cancer survivorship reported, the risk for death from most other non-cancer causes of men with distant prostate cancer was heightened.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous analysis showed that non-cancer causes covered 6.9% of patients diagnosed with malignant cancer with synchronous bone metastases. Common non-cancer COD included cardiovascular and cerebrovascular diseases, COPD and associated conditions, and septicemia, infectious and parasitic diseases [5] . The population-based cohort study based on the SEER database focusing on the COD during prostate cancer survivorship reported, the risk for death from most other non-cancer causes of men with distant prostate cancer was heightened.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we conducted a pan-cancer analysis among eighteen different cancer types. The classification of cancer types was defined according to the variable of 'Site recode ICD-O-3/WHO 2008', which was described in our previous article [5] . The mortality trend and COD among pan-cancer were analyzed and visualized.…”
Section: Primary Tumors and Cause Of Death Datamentioning
confidence: 99%
See 1 more Smart Citation